Trace metal mobilization by organic soil amendments: insights gained from analyses of solid and solution phase complexation of cadmium, nickel and zinc. (May 2018) - Welikala, Dharshika; Hucker, Cameron; Hartland, Adam; Robinson, Brett H.; Lehto, Niklas J.
Abstract: The accumulation of Cd in soils worldwide has increased the demand for methods to reduce the metal's plant bioavailability. Organic matter rich soil amendments have been shown to be effective in achieving this. However, it is not known how long these amendments can retain the Cd, and whether dissolved organic matter (DOM) released from them can enhance the metal's mobility in the environment. In this study we sought to test the Cd binding capacity of various organic soil amendments, and evaluate differences in characteristics of the DOM released to see if they can explain the lability of the Cd-DOM complexes. We collected ten organic soil amendments from around New Zealand: five different composts, biosolids from two sources, two types of peat and spent coffee grounds. We characterised the amendments' elemental composition and their ability to bind the Cd. We then selected two composts and two peats for further tests, where we measured the sorption of Ni or Zn by the amendments. We analysed the quality of the extracted DOM from the four amendments using 3D Excitation Emission Matrix analysis, and tested the lability of the metal-DOM complexes using an adapted diffusive gradients in thin-films (DGT) method. We found that composts bound the most Cd and that the emergent Cd-DOM complexes were less labile than those from the peats. Ni-DOM complexes were the least labile. The aromaticity of the extracted DOM appears to be an important factor in determining the lability of Ni complexes, but less so for Zn and Cd. Graphical abstract: Image 1 Highlights: Adapted DGT method measures complex lability in small volumes. Composts bind Cd effectively, but may mobilize trace metals via DOM-complexes. Nickel complexes are less labile than Cd or Zn complexes in compost extracts. Aromatic DOM reduce lability of Ni complexes, and Zn to a lesser extent.